2017
DOI: 10.1016/j.radonc.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfractionated accelerated reirradiation for rectal cancer: An analysis of outcomes and toxicity

Abstract: This large, retrospective, single-institution study shows that hyperfractionated accelerated reirradiation was well tolerated. The rate of FFLP was promising, given that the study comprised heavily pre-treated patients with recurrences. Rates of FFLP and OS were particularly impressive in patients who underwent both reirradiation and surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…We have previously advocated for the use of limited RT fields (tumor + 2-3 cm margin) for reirradiation in the setting of recurrent rectal cancer. 19 , 20 However, in the current series, 8 of 10 patients were given reirradiation to an elective nodal volume in addition to the primary tumor. Our rationale was that primary rectal cancer after other malignancies is a very different clinical entity compared with recurrent rectal cancer and the pattern of failure is likely to be locoregional for primary rectal cancer and local for recurrent rectal cancer.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We have previously advocated for the use of limited RT fields (tumor + 2-3 cm margin) for reirradiation in the setting of recurrent rectal cancer. 19 , 20 However, in the current series, 8 of 10 patients were given reirradiation to an elective nodal volume in addition to the primary tumor. Our rationale was that primary rectal cancer after other malignancies is a very different clinical entity compared with recurrent rectal cancer and the pattern of failure is likely to be locoregional for primary rectal cancer and local for recurrent rectal cancer.…”
Section: Discussionmentioning
confidence: 82%
“…In a recent study, we reported a 3-year FFLP rate of 40%, and a 3-year OS rate of 39% in 102 patients who were treated with reirradiation for recurrent rectal cancer. 20 However, the rates of FFLP and freedom from any progression appear to be lower than those typically expected for de novo rectal cancer. Inferences are difficult to draw from a small series such as this, but our results do raise the question of whether rectal cancer in the setting of prior pelvic radiation carries a worse prognosis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Advancements in radiotherapy have allowed conformal radiation dose distribution with delivery of incremental doses to tumors and a minimal dose to adjacent critical structures. Re-irradiation has shown satisfactory clinical outcome in certain recurrent tumors such as lung cancer, head and neck cancer, high-grade glioma, and rectal cancer [ 6 11 ]. In the present study, we evaluated the clinical prognostic factors associated with overall survival (OS) in recurrent ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no established standard for re-irradiation of recurrent rectal cancer much due to the lack of knowledge about late morbidity after radiotherapy, although hyper-fractionated RT has been shown to be feasible [19][20][21][22][23]. Most previous studies have been conducted with older techniques such as two lateral opposing fields, 3-field techniques, or 3D conformal radiotherapy [19][20][21]24,25]. However, CBCT-guidance allows for smaller margins and may in combination with the conformity of IMRT and VMAT significantly limit normal tissue dose.…”
Section: Discussionmentioning
confidence: 99%